EXPEDITED PRESERVATION OF STORED COMPUTER DATA - Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Due to the development and ubiquity of information technology in everyday life, the number of criminal activities committed using computer systems and networks has also increased. Traces of the crimes committed in connection with the misuse of information technologies are in the form of electronic records - computer data that occur as a result of the actions of the perpetrator or as automatically created and stored in a computer system / network. However, these computer data are subject to change , so it is necessary to adequately ensure their protection. To create an appropriate legal framework to counter these challenges , the rules of criminal procedure law have to determine the appropriate powers of the competent authorities for the purpose of collecting and providing computer data on the committed criminal offense and the offender can be used as electronic evidence in criminal proceedings.